Y-balance test performance and BMI are associated with ankle sprain injury in collegiate male athletes. Issue 7 (July 2018) - Hartley, Emily M.; Hoch, Matthew C.; Boling, Michelle C.
Abstract: Objectives: To determine if static balance, dynamic balance, ankle range of motion, body mass index (BMI), or history of an ankle sprain were associated with ankle sprain injuries within male and female collegiate athletes. Design: Prospective cohort. Methods: Three hundred and eighty-four male (age = 19.79 ± 1.80 years, height = 178.02 ± 10.39 cm, mass = 85.71 ± 17.59 kg) and one hundred and sixty seven female (age = 19.80 ± 1.52 years, height = 165.61 ± 7.08 cm, mass = 66.16 ± 10.53 kg) collegiate athletes involved in a variety of sports at a NCAA Division II or NAIA institution participated. Baseline measures of the Y-Balance (YBT), modified Balance Error Scoring System (mBESS), weight-bearing lunge test (WBLT), BMI, and history of ankle sprain were recorded. Participants were followed prospectively for two years and incidence of ankle sprain injury was documented. The average of the WBLT, mBESS, and YBT measures were used for analysis. Male and female participants were analyzed separately. Mann–Whitney U tests were utilized to identify variables which may be significantly associated with ankle sprain injury for logistic regression analysis. Results: A total of 59 (38 males and 21 females) individuals sustained an ankle sprain during the follow up period. The binary logistic regression revealed BMI (Nagelkerke R 2 = 0.069; X 2 = 12.89; p < 0.001; OR = 3.85; 95% CI, 1.90–7.79; p < 0.001) and anterior reach of the YBT (Nagelkerke R 2 = 0.074; X 2 = 13.70, p < 0.001; OR = 3.64; 95% CI = 1.83–7.23; p = 0.01) were significantly associated with ankle sprain injury in male athletes. No variables were associated with ankle sprain injury within female athletes. Conclusions: Male collegiate athletes with greater BMI and lesser YBT anterior reach were at a greater risk of sustaining an ankle sprain injury.